The Use of A Compound Based on Phyllosilicates and Cinnamon Essential Oil for Chicken Broiler’s Litter - Marchioro,T (2022)
ABSTRACT The objective of this study was to evaluate the effectiveness of a litter conditioning compound (LCC) based on 98% phyllosilicates (kaolinite) and 2% cinnamon essential oil to be applied on the litter of broiler houses. Animal performance, prevalence of footpad lesions, and litter quality (water activity, pH, and moisture) were evaluated, in addition to the effect on the incidence of Salmonella spp., evaluated by testing shoe-drag swabs, fecal samples, and organs. Twenty-one broiler houses with similar structure and rearing conditions were distributed in a completely randomized design with three treatments and seven replications each, as follows: T0: control, without the use of LCC; T100: application of 100 grams of LCC per m² of litter per week; T200: application of 200 grams of LCC per m² of litter per week. There was no significant effect of treatments on performance variables; however litter pH was lower when 200g/m2 was used in comparison with the control treatment, a result not verified for moisture and water activity (p>0.05). Our findings demonstrated significant reduction in the percentage of footpad lesions in birds that received the LCC (T0: 63.37%; T100: 41.38% and T200: 27.24%). A reduction in the number of positive flocks for Salmonella spp. Was also observed (with overall positivity rates of 17.86%, 12.14%, and 5% for treatments T0, T100, and T200, respectively). It is concluded that the product reduces the incidence of Salmonella spp. and also significantly reduces the incidence of footpad lesions, two important factors for the poultry industry.